Alcohol extract of Schinu sterebinthifolius raddi (anacardiaceae) as a local antimicrobial agent in severe autogenously fecal peritonitis in rats - Melo,Maria Cecília Santos Cavalcanti (2014)
PURPOSE: To develop an alcoholic extract of the inner bark of the Schinus terebinthifolius raddi and to test its impact on autogenously fecal peritonitis in Wistar rats. METHODS: The inner bark of the Schinus terebinthifolius raddi was kept for seven days in 70% ethanol alcohol. The total elimination of the solvent was performed in a rotary evaporator under reduced pressure at 55-60°C. Four milliliter of this extract was injected, after 24 h, into the abdominal cavity of six out of eight survival rats that underwent autogenously fecal peritonitis with five milliliter of 10% filtered fecal suspension. They were clinically followed up for 45 days when they were euthanized. The necropsy findings (inventory) of the abdominal and thorax cavities were inspected and the main findings were recorded and photographed. The investigation was approved by the Ethics Committee. RESULTS: Two out of six survival rats that were critically ill after 24 h died within the 12 h after the extract injection into the abdominal cavity. Four rats that were also critically ill recovered and gradually became healthy, eating well, regaining weight and moving normally in the cage. At 45 days post severe peritonitis the necropsy findings revealed few signs of residual infection on the abdominal and thorax cavities. There were no bowel adhesions. CONCLUSION: The impact of alcoholic extract of the inner bark of the Schinus terebinthifolius raddi was considered very positive and promising as natural local antiseptic against very severe peritonitis in Wistar rats.